2008
DOI: 10.1103/physreve.77.031107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time delay on symmetric two-species competition subject to noise

Abstract: Noise and time delay act simultaneously on real ecological systems. The Lotka-Volterra model of symmetric two-species competition with noise and time delay was investigated in this paper. By means of stochastic simulation, we find that (i) the time delay induces the densities of the two species to periodically oscillate synchronously; (ii) the stationary probability distribution function of the two-species densities exhibits a transition from multiple to single stability as the delay time increases; (iii) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…A single-mode laser cubic model driven by quadratic pump noise was investigated by Cao and Wu, and the same phenomenon was found at the boundary I = 0 [61]. Further, this phenomenon was found in a two-dimensional dynamic system [46].…”
Section: The Euler Differential Equation Of General Time-delayed Modelmentioning
confidence: 77%
See 1 more Smart Citation
“…A single-mode laser cubic model driven by quadratic pump noise was investigated by Cao and Wu, and the same phenomenon was found at the boundary I = 0 [61]. Further, this phenomenon was found in a two-dimensional dynamic system [46].…”
Section: The Euler Differential Equation Of General Time-delayed Modelmentioning
confidence: 77%
“…Rosenblum and Pikovsky suggested that time-delayed feedback can be used for the purposes of deep brain stimulation such as suppression of pathological brain rhythms [44]. Nie and Mei displayed that a time delay can suppress a population explosion [45], synchronous oscillation, a first-order-like transition and the nonmonotonic behavior of the characteristic correlation time caused by the time delay [46] in the Lotka-Volterra model. It was found that a longer time delay results in a less stable system of the predator-prey-type ecosystem [47] by Cai and Lin.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of time delay in competitive systems in the ecological field have been also studied. The results imply that the combination of noise and time delay could provide an efficient tool for understanding real ecological systems [8]. The delay time also induces stochastic oscillations in gene regulation [9].…”
mentioning
confidence: 88%
“…For this phenomenon, according to Ref. [50], it implies that coherence resonance phenomenon with respect to non-Gaussian noises occurs in cytosol. Recently, coherence resonance has been studied in the twodimensional system [51][52][53][54].…”
Section: Naf and Cct Of Intracellular Ca 2+ Concentrationmentioning
confidence: 99%